Capitalization for whom?: The PFAs System - Cruz Saco, María Amparo (1999)
We simulate rates of return, administration fees and market shares for the five private pension fund managers that constitute the Peruvian AFP industry. After five years of operation and payment of costs related to the introduction of individual pension accounts and the financial strengthening of private managers, the oligopoly reaches high profitability rates. Transactional costs remain high due to lack of competition. Since its inception, affiliates have earned negative returns on their old-age savings thus motivating non-payment of mandatory contributions and the increased "informalization" of the labor force. Oldage coverage (AFPs and the public scheme) is only 30% of the labor force mainly for dependent and high-income workers. Two thirds of the labor force continues without coverage.   Thus, the pension system requires a profound restructuring to address issues such as the introduction of new products, competition, reducing high opportunity costs, the principal agent problem and moral hazard due to the absence of a minimum pension in the private scheme.